The Application Of The WP (Weighted Product) Method In The Decision Support System Of Determining Bonus Employees (STUDY CASE: CV. Arsmas Suan Sejahtera) - Rimmar Siringoringo (Cattleya Darmaya Fortuna, 2023)
Decision support systems are part of a computer-based information system including knowledge-based systems or knowledge management that are used to support decision making in an organization or company. It can also be said as a computer system that processes data into information to make decisions on specific semi-structured problems. The Weighted Product method is part of the Fuzzy Multi Attribute Decision Making (FMADM) concept which requires normalization of the calculations. By using the Weighted Product method, it is hoped that a decision support system software can be developed that can be used by an agency, which will be an alternative selection and give weight to alternative comparisons and criteria, while these criteria are discipline, responsibility, loyalty and quality of work. The criteria have been determined by the company. The results of the study show the use of Weighted Products as a model for a decision support system for determining employee bonus recipients at CV. Arsmas Suan Sejahtera can assist company owners in determining employees who are entitled to be recommended for multi-criteria weighting bonuses and selection more quickly, accurately and more effectively.